2010
DOI: 10.1364/oe.18.005413
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave laser operation of Tm and Ho
 co-doped NaY(WO_4)_2 and NaLu(WO_4)_2 crystals

Abstract: Tetragonal single crystals of NaT(WO(4))(2) (T = Y or Lu) co-doped with Tm(3+) and Ho(3+) ions have been employed for broadly tunable and efficient room-temperature laser operation at around 2 mum. With Ti:sapphire laser pumping at 795 nm, a slope efficiency and a maximum output power as high as 48% and 265 mW, respectively, have been achieved at 2050 nm from a Tm,Ho:NaY(WO(4))(2) crystal. Tuning from 1830 nm to 2080 nm has also been obtained using an intracavity Lyot filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…1a) even for inversion rates as high as 0.5. In a recent report on the same co-doping but in a different host [20], the authors observed net gain of Ho in this spectral region but this seems not to be the case for the KLuW host. Fig.…”
Section: Laser Experimentsmentioning
confidence: 84%
“…1a) even for inversion rates as high as 0.5. In a recent report on the same co-doping but in a different host [20], the authors observed net gain of Ho in this spectral region but this seems not to be the case for the KLuW host. Fig.…”
Section: Laser Experimentsmentioning
confidence: 84%
“…[27][28][29] It is interesting to observe that, although NaGd(WO 4 ) 2 has the largest phonon threshold among the three materials, it demonstrates the strongest green 2 H 11/2 / 4 S 3/2 -4 I 15/2 UCL in the materials, and its intensity is enhanced as high as 120 times that of the wellknown Y 2 O 3 :Yb 3+ /Er 3+ . The high-excitation cross section of Yb 3+ at 980 nm, high optimum concentrations of Yb 3+ and Er 3+ and the modulation of large phonon energy on the population of the green level are capable of efficient UCL.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, efficient laser operation with Nd 3þ [6], Yb 3þ [7,8], Tm 3þ [9,10] and Ho 3þ ions [11] has been reported. These materials have an important advantage as compared with their monoclinic counterparts where Na þ is replaced by K þ , i.e.…”
Section: Introductionmentioning
confidence: 99%